?????? ????? ?????? ?????? ???? ????? ???????? ??????? ????? ???????? Fishbowl ????? - Siti Qonita Latifah; Ali Wafa (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2019)
The process of teaching Arabic in MTs Hasyim Ash'ari Ash-Nahdiyyah Sedati Sidoarjo is a traditional learning process, where the teacher uses the lecture method to teach speaking skills. The background of this research is the teacher does not have the appropriate innovation and model, while in the learning process requires the use of appropriate learning theories so that students do not feel difficulties and can obtain material more effectively and efficiently. This research uses quantitative methods. The data collection methods are: observation method, test method and document. As for the research sample, it was 22 students in seventh grade. From this study it can be seen an increase in kalam skills in students after applying the Fishbowl method. with the analysis obtained with the t-test: t_0 results are 9,088 and tt is 1,720 because t_0 is greater than tt then the hypothesis zero (Ho) is rejected and the alternative hypothesis (Ha) is acceptable.